PENGARUH SERVICE QUALITY DAN INTERPERSONAL COMMUNICATION TERHADAP KEPUASAN KONSUMEN: Studi Pada Showroom Hartono Mobil - Dunan, Hendri; Hartono, Celine Viona (Media Mahardhika, 2025)
People's lives today have undergone major changes compared to the past, especially due to the rapid advancement of technology, changing trends and consumer preferences in the automotive industry are often influenced by external factors such as government policies, economic conditions and technological innovation. “This study was conducted to determine the effect of Service Quality and Interpersonal Communication on customer satisfaction of Hartono car showroom. The method in this study is quantitative and there are 49 respondents who are Hartono showroom consumers. Data analysis through Statistical Package for the Social Sciences (SPSS). The result is that Service Quality has no effect on customer satisfaction. Interpersonal Communication has a positive and significant effect on Customer Satisfaction, Service Quality and Interpersonal Communication together, have a positive influence on Customer Satisfaction.